"A Land that Devours Its Inhabitants": Midrashic Reading, Emmanuel Levinas, and Prophetic Exegesis - Goodhart, Sandor ca. 20./21. Jh. (Shofar, 2008)
This essay initially cites the ways Levinas has been read to date—in philosophy, feminism, and Jewish Studies—noting the absence of midrashic reading, and especially one identified as akin to literary reading. It next defines midrash as the Rabbis and Jewish Studies scholars describe it (for example, in Genesis 22), and proceeds to examine a sample of midrashic reading—Levinas's "Promised Land or Permitted Land?"—perusing this text in four ways: (1) for the Biblical scripture (in Numbers, Deuteronomy, and Isaiah) the Talmudic rabbis read; (2) for the Talmudic commentary in Sotah that Levinas examines; (3) for Levinas's ethical commentary; and (4) for my own prophetic account of Levinas's commentary upon Talmud's scriptural reading. These four roughly correspond, the essay suggests, with the four traditional levels of interpretation—pshat, remez, d'rash, and sod—about which the Rabbis speak or the four levels about which Christian hermeneuts speak: plain sense, allegorical, moral, and anagogic.